Predictors of Intervention Adherence among Young People Living with HIV - Song, Juwon (2006)
Objective: To examine adherence to a 23 session intervention for young people living with HIV. Methods: 208 HIV-positive youth were assigned by small cohort to a behavioral intervention. Results: Youth with more personal strengths were more likely to attend the intervention; those with more competing environmental demands (e.g., employment, school) were less likely to attend the intervention. Using a social support, spiritual hope, or self-destructive and escape coping style was associated with attendance. Youth who reported many sexual partners attended fewer sessions. Adherence varied by cohort assignment. Conclusion: When designing future interventions, high attendance should be considered as a goal.